3 - Revealed Preference Theory, Rationality, and Neoclassical Economics: Science or Ideology - Keita, Lansana (Africa Development, 2021)
Revealed Preference Theory (Samuelson 1938) is an attempt to establish economic theory as a genuine empirical science by ridding it of non- empirical psychological concepts. Samuelson’s goal was to rid economic theory of the last vestiges of utility analysis. Samuelson structured his theory on a set of preference axioms that would explain the choices of economic agents. But revealed preference theory is rendered problematic because decision making is structured therein on preferences that conform to an implicit postulate of rationality. Matters are further compounded by the fact that despite theoretical support offered by theorists such as Varian, the empirical results demonstrate that agent decision making is often at variance with the formal axioms of revealed preference. The issue is not solved even when decision making is construed within the context of imperfect, that is, ‘bounded rationality’. I argue that neoclassical economic theory is best understood as a form of rule utilitarianism. In this regard, neoclassical economics is unavoidably value-laden and should be construed as an aspect of normative welfare economics. Thus efforts by theorists such as Vanberg to salvage the assumed scientific credentials of neoclassical economics by construing the postulate of rationality in evolutionary terms are seen as problematic. Neoclassical economic theory is to be viewed essentially then as an ideology that presents a particular theory of human behaviour. It is this theory that serves as the foundations of modern capitalism and its practise as neoliberal economics. This is the anthropological question then: is such an ideology socially optimal for humans as social animals in terms of efficiency and equity?